Observation of Magnetic Field‐Induced and Partially Switchable Electric Polarization in Spin‐Chain FePbBiO4 - Ajay Tiwari; D. Chandrasekhar Kakarla; Wei‐Lin Chen; C. Dhanasekhar; Ya‐Jing Hu; Jiunn‐Yuan Lin; Chin‐Wei Wang; Ting‐Wei Kuo; Arkadeb Pal; Mitch Ming‐Chi Chou; Hung‐Duen Yang (Advanced Physics Research)
Abstract The linear magnetoelectric (ME) characteristics of a quasi‐1D spin‐chain compound, FePbBiO4, are reported. Two distinct antiferromagnetic (AFM) orders occurring at ≈23 K (TN1) and 12 K (TN2) are verified using magnetization, specific heat, and conspicuous dielectric (ε′) anomalies. A striking observation is that no pyrocurrent (Ipy) is detected in the absence of magnetic field (H); however, H‐induced ferroelectric polarization (P) at TN1 and P unexpectedly partially switches or reverses below TN2 as reproduced by applying positive and negative electric fields (E). The resulting magnetic field and temperature (H‐T) phase diagram illustrates T‐dependent H‐induced spin reorientation and electric P. The interaction between T, H, spin dynamics, and lattice structures is pivotal and is qualitatively discussed and proposed as an explanation for the observed ME nature.